2013
DOI: 10.1177/1350650113504908
|View full text |Cite
|
Sign up to set email alerts
|

A review of fingerpad contact mechanics and friction and how this affects tactile perception

Abstract: In the sliding contact between the fingerpad and a rough surface when touching a product’s surface, friction plays a role in the perception of roughness, slipperiness and warmth. For product engineers who aim to control and optimize the sensorial properties of a product surface interacting with the skin, it is essential to understand this frictional behaviour. However, the friction of skin is yet poorly understood. The variation that is observed within or between skin friction studies can be assigned to gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 70 publications
5
68
0
Order By: Relevance
“…The present images are consistent with those reported by Childs & Henson [16], but perhaps because of the poor quality of the ink print images, their significance was under-appreciated. Our results also indicate that friction, driven by the growth dynamics of the real area of contact, may play a determining role in the perception of roughness, slipperiness, and warmth, as recently reviewed in reference [12].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present images are consistent with those reported by Childs & Henson [16], but perhaps because of the poor quality of the ink print images, their significance was under-appreciated. Our results also indicate that friction, driven by the growth dynamics of the real area of contact, may play a determining role in the perception of roughness, slipperiness, and warmth, as recently reviewed in reference [12].…”
Section: Discussionsupporting
confidence: 80%
“…Hence, surfaces may be viewed to be composed of features at multiple length scales of roughness that are superimposed on each other [11]. A number of studies have examined the influence of the topography of counter-surfaces on the friction of the finger pad [12]. For regular counter surface textures, it was observed that the coefficient of friction increased with the tip radius and number density of the asperities as would be expected by the resulting increase in the real area of contact [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study of friction and the role of surface textures in relation to touch perception is the subject of researches in both science and industry for a wide variety of applications (van Kuilenburg et al, 2013;Derler et al, 2009;. Tactility is directly related to the functional behavior and perception of products like haptic devices, smartphone cases, tool handles, personal care products and for example kitchenware.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, the surface was smoothly finished. The surface roughness and friction are closely related [45,46]. Because of the interlocking effects, surfaces with significant roughness develop large friction forces with a fingertip.…”
Section: Conditions Causing Lateral Vibration To Increase Friction Pementioning
confidence: 99%